2023
DOI: 10.1111/1365-2656.13889
|View full text |Cite
|
Sign up to set email alerts
|

The non‐random assembly of network motifs in plant–pollinator networks

Abstract: Ecological processes leave distinct structural imprints on the species interactions that shape the topology of animal–plant mutualistic networks. Detecting how direct and indirect interactions between animals and plants are organised is not trivial since they go beyond pairwise interactions, but may get blurred when considering global network descriptors. Recent work has shown that the meso‐scale, the intermediate level of network complexity between the species and the global network, can capture this importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…We considered subgraph-level processes because it has been recently suggested that they may be particularly important for analyzing the functional consequences of community structure: at that scale, the local patterns of realized direct interactions can reveal the different mechanisms through which individual- and species-based nodes can indirectly influence each other (Simmons et al ., 2018) and it has been shown that some sub-graphs are over-represented in plant-pollinator networks (i.e. form distinctive motifs) (Lanuza et al ., 2023). For the network-level structure, we calculated (i) the modular partitions that better describe network information flows (subsection “Modularity”).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…We considered subgraph-level processes because it has been recently suggested that they may be particularly important for analyzing the functional consequences of community structure: at that scale, the local patterns of realized direct interactions can reveal the different mechanisms through which individual- and species-based nodes can indirectly influence each other (Simmons et al ., 2018) and it has been shown that some sub-graphs are over-represented in plant-pollinator networks (i.e. form distinctive motifs) (Lanuza et al ., 2023). For the network-level structure, we calculated (i) the modular partitions that better describe network information flows (subsection “Modularity”).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…(2019) highlighted the limits of macro‐scale metrics for capturing structural differences between bipartite networks and showed the usefulness of motifs (a small subset of species interactions exhibiting varying topologies), which capture the mesoscale structure (Milo et al., 2002). Motifs have been informative in various contexts, like the assessment of network stability, the resistance to biological invasions (Losapio et al., 2021; Milo et al., 2002; Stouffer & Bascompte, 2010; Vitali et al., 2022), or the characterization of the singular positions of functional groups (Lanuza et al., 2023). Another way to characterize the structure of interaction networks is through the spectral densities of the Laplacian graph representing each interaction network.…”
Section: Introductionmentioning
confidence: 99%
“…Simmons, Cirtwill, et al, (2019) highlighted the limits of macro-scale metrics for capturing structural differences between bipartite networks and showed the usefulness of motifs (a small subset of species interactions exhibiting varying topologies), which capture the mesoscale structure (Milo et al, 2002). Motifs have been informative in various contexts, like the assessment of network stability, the resistance to biological invasions (Losapio et al, 2021; Milo et al, 2002; Stouffer & Bascompte, 2010; Vitali et al, 2022), or the characterization of the singular positions of functional groups (Lanuza et al, 2023). Another way to characterize the structure of interaction networks is through the spectral densities of the Laplacian graph representing each interaction network.…”
Section: Introductionmentioning
confidence: 99%